Unusual trisulphide linkage in bromine-thiourea reaction: crystal structure of formamidinium trisulphide complex with bromine - Tol, Abhaya D.; Natu, Arun D.; Puranik, Vedavati G. (Molecular Crystals and Liquid Crystals, 2007)
{A new complex of formamidinium trisulphide with bromine has been synthesized. Single-crystal X-ray analysis of this compound revealed a novel trisulphide linkage in the formamidinium trisulphide moiety. The crystals belong to orthorhombic space group Fdd2 with a = 14.9119(15)
Keywords: bromine; crystal structure; formamidinium trisulphide; thiourea

Bromine-induced facile synthesis of butenolides and spirobutenolides from sterically congested tetrasubstituted dialkyl alkylidene succinates - Patel, Ramesh M.; N. P. Argade (Synthesis-Stuttgart, 2010)
Starting from sterically congested tetrasubstituted dialkyl alkylidene succinates, facile general approach to several dialkyl substituted butenolides and spirobutenolides with the generation of quaternary carbon center has been demonstrated via bromine-induced dealkylative regioselective intramolecular cyclization and dehydrobromination pathway. The mechanistic aspects involved in the formation of butenolides have been also described in brief.
Keywords: alkylidene succinates; bromine; butenolides; intramolecular cyclizations; spirobutenolides